TRANSMISI DAN REAKTIVASI VIRUS HERPES SIMPLEKS TIPE 1 (LAPORAN KASUS) - Nendika Dyah Ayu Murika Sari; Eki Dyan Larasakti (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2021)
Background : Herpes simplex virus (HSV) type 1 can cause recurrent infection (reactivation) in the form of herpes labialis. This viral infection can be transmitted through contact with oral secretions, with a 8-10% prevalence of patients) and 90% of close contact with patients. The purpose of this case study is to describe herpes labialis caused by contact with the patient and its treatment. Case report : A 23-year-old woman came to RSIGM Sultan Agung Semarang with the chief complaint of sores in the corner of her mouth since 4 days ago with fever, which ruptured two days later. Extraoral examination revealed 4 mm erosions with clear borders and multiple 1 mm vesicles with clear borders surrounded by erythematous based on the labial commissure dextra. Herpes labialis was diagnosed. Conclusion : Herpes labialis can be transmitted through direct contact or through oral secretions such as saliva. Giving acyclovir cream three times a day is effective for relieving symptoms and hastening healing. These lesions can be healed without scar.